Prosedur Pengadaan Barang Dan Jasa Di PT Alfitra Rayavespindo - Umi Zunaidah; Johan Lucas Away; Andi Nurhasanah; Irgi Voller Away (Politeknik Negeri Samarinda, 2021)
The problem discussed is about the Procedure for the Procurement of Goods and Services carried out by the Administrative Section at PT Alfitra Raya Vespindo. The purpose of this study was to determine the process of the procurement of goods and services carried out by the Administrative Section at PT Alfitra Raya Vespindo. The data collection method used is the method of observation, interviews, and literature study. The analysis tool uses the opinion expressed by Christopher & Schonner (2007) in their book entitled